Polynitrocarbamates Derived from Nitromethane. Issue 21 (6th September 2017) - Klapötke, Thomas M.; Krumm, Burkhard; Reith, Thomas
Abstract : A variety of energetic compounds combining nitro with nitrocarbamate groups were synthesized. The precursors, polynitro alcohols, were obtained by the condensation of the readily available starting material nitromethane with the small aliphatic aldehydes formaldehyde and glyoxal. The conversion into carbamates was achieved with the reactive chlorosulfonyl isocyanate (CSI) and a final nitration yielded the polynitrocarbamates. The new compounds were fully characterized, including multinuclear NMR spectroscopy, vibrational analysis, mass spectrometry, differential scanning calorimetry, and elemental analysis. The energies of formation were calculated with the GAUSSIAN program package and the detonation parameters were predicted using the EXPLO5 computer code. Due to the positive oxygen balance ( Ω CO ) of the presented compounds, their performance data as oxidizers were determined and compared to the common oxidizer ammonium perchlorate. Abstract :